Web Based Automated Smart House Management - Navya Navya; Ganesh Dumala (Institute of Advanced Engineering and Science, 2015)
A Home automation refers to control appliances around the home. These appliances can include lights, fans and other electronic devices. Instead of using GSM and ZIGBEE modules use a simple system to reduce complexity. Here the proposed system uses web server using microcontroller. The proposed system gives users an effective and easy way of controlling the various home appliances from a remote location i.e. without physically being present at home. This system can control the fans and lights. Microcontroller is used to acquire data from different types of sensors. It can monitor the appliances from anywhere with the help of web page. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7173